Economic Reforms and Productivity-Enhancing Reallocation in the Post-Soviet Transition - J. David Brown; John S. Earle (W.E. Upjohn Institute for Employment Research, 2004)
How do economic reforms affect resource reallocation processes and their contributions to productivity growth? This paper studies the consequences of enterprise privatization and liberalization of product markets, labor markets, and imports in the former Soviet Republics of Russia and Ukraine. Analyzing interfirm reallocation of output, labor, capital, and an input index with annual industrial census data from 1985 to 2001, we find that Soviet Russia displayed low reallocation rates that bore little relationship to relative labor and multifactor productivity across firms. Since reforms began, resource flows have increased in both countries, and their contributions to aggregate productivity growth have become substantial through increased flows from less productive to more productive continuing firms and through higher exits of less productive entities - i.e., through creative destruction. Among the policy factors that may explain firm-level variation, privatization is estimated to have positive effects on productivity-enhancing reallocation, but there is less evidence of such effects from domestic product market competition, labor market competition, or import penetration.
Keywords: E24; J63; O47; P23; 330; interfirm; reallocation; post-Soviet; Ukraine; Russia; Earle; Brown